2020
DOI: 10.1002/adsu.202000110
|View full text |Cite
|
Sign up to set email alerts
|

High Capacity Functionalized Protein Superabsorbents from an Agricultural Co‐Product: A Cradle‐to‐Cradle Approach

Abstract: Synthesis of superabsorbent particles from nontoxic wheat gluten (WG) protein, as an industrial co‐product, is presented. A natural molecular cross‐linker named genipin (a hydrogenated glycoside) is used together with a dianhydride (ethylenediaminetetraacetic EDTAD), to enable the preparation of a material with a network structure capable of swelling up to ≈4000% in water and ≈600% in saline solution. This represents an increase in swelling by over 10 times compared to the already highly absorbing gluten refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 68 publications
4
25
0
Order By: Relevance
“…). Previous work has demonstrated that the addition of genipin significantly increases the water uptake in various biopolymer materials. To investigate if the whey PNF materials show the same behavior, we measured the water uptake in samples with 5% or 10% genipin (reacted under similar conditions to those in the microfibers) and compared it with the material without genipin. The water content was quantified by thermogravimetric analysis (TGA) (Figure S3) and was found to be 6.2%, 5.6%, and 5.1% for the samples with 0%, 5%, and 10% genipin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…). Previous work has demonstrated that the addition of genipin significantly increases the water uptake in various biopolymer materials. To investigate if the whey PNF materials show the same behavior, we measured the water uptake in samples with 5% or 10% genipin (reacted under similar conditions to those in the microfibers) and compared it with the material without genipin. The water content was quantified by thermogravimetric analysis (TGA) (Figure S3) and was found to be 6.2%, 5.6%, and 5.1% for the samples with 0%, 5%, and 10% genipin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We recorded nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR), and XPS spectra to confirm the structures of our PDs. A comparison of the 1 H NMR spectra of BCDA, EDTAD, Jeffamine T-403, and the PDs revealed that only those of the PDs featured signals at 7.94 ppm, representing the H atoms of their amido groups (Figure a–e). Figure S3a displays the FTIR spectra of BCDA and EDTAD, featuring signals for the symmetric and asymmetric stretching of their CO units in the ranges 1761–1774 and 1809–1822 cm –1 , respectively. , After the dianhydrides had reacted with the triamine to form poly­(amic acid)­s with amido and carboxyl groups, Figure S3b reveals that the FTIR spectra of PD-BT-12 and PD-ET-12 lacked any signals for symmetric and asymmetric stretching of the CO units of the dianhydride but signals had emerged for amide I and II vibrational modes in the ranges 1543–1560 and 1657–1663 cm –1 , respectively …”
Section: Resultsmentioning
confidence: 99%
“…For the sample without glycerol (LPI-0-commercial) smaller d1 and d2 values were observed in comparison to the other samples ( Table 1 ), which indicate a differently organized system in the absence of glycerol. Glycerol with its three functional hydroxy groups per molecule is known to easily embedd and interact with the lupin protein matrix and connect to protein chains due to steric interactions [ 20 , 21 ], that plasticized and arranged the protein. Previous studies on gliadin have shown that the presence of glycerol drives the gliadins into a more organized state, less susceptible to polymerization [ 16 ].…”
Section: Resultsmentioning
confidence: 99%